Fiscal sustainability and public debt in an endogenous growth model - Jesús Fernández-Huertas Moraga; Jean-Pierre Vidal (European Central Bank (ECB), 2004)
This paper investigates fiscal sustainability in an overlapping generations economy with endogenous growth coming from human capital formation through educational spending. We assess how budgetary imbalances affect economic dynamics and the outlook for economic growth, thereby providing a rationale for fiscal rules ensuring sustainability. Our results show that the appropriate response of fiscal policy to temporary shocks is not trivial in the absence of fiscal rules. Fiscal rules allow for a timely reaction, thereby avoiding possibly disruptive fiscal adjustment in the future: the more adjustment is delayed, the larger is its necessary scale. We perform a rough calibration of the model to simulate the effects of a demographic shock (change in the population growth rate) under different fiscal policy scenarios.
Keywords: E62; H63; H55; O41; E17; 330; Fiscal sustainability; overlapping generations; public debt